“Common but differentiated responsibilities: an exploration of the concepts of equitable evolution and graduation within the climate change treaty system” - Koketso, Sakhile (Institute of Marine and Environmental Law, 2026)
In light of the growing urgency for action on climate change and the stagnation of negotiations within the climate change regime, the study closely examines the content, legal status and operation of principle of common but differentiated responsibilities, which is assumed to be one of the biggest stumbling blocks in achieving an effective climate change treaty system. The study also analyses the link between the principle and the notions of evolution of the treaty system and graduation of developing countries that have reached an advanced stage of development, and suggests ways in which these can be implemented in a fair and equitable manner.